ANALISIS PERUBAHAN KERAPATAN HUTAN KOTA PEKANBARU TAHUN 2018 DAN 2022 MENGGUNAKAN CITRA LANDSAT 8 OLI/TIRS - Hidayat, Teguh; Ernawati, Ernawati (JURNAL BUANA, 2025)
Changes in forest density from year to year are caused by spatial factors and are expected to be used as supporting data to control land conversion in order to maintain a spatial layout that continues to provide comfort. The city is a place that is the center of human activity. This research uses quantitative research methods, while the research method used is descriptive methods. Descriptive research involves describing phenomena that exist, are occurring or have occurred in the past. Landsat 8 OLI/TIRS imagery for 2018 and 2022 is a tool for understanding changes in the size and shape of forest density. Based on the results of research conducted in Pekanbaru City to determine forest productivity from 2018 to 2022, there are five levels of forest productivity: Very Rare, Rare, Medium, Low and Very High.